Ethnic Self-Consciousness and Interethnic Relations in the Poly-Ethnic Region: A Research in Tatarstan - Gibadullin, Rustam; Asratyan, Norair; Asratyan, Zoya; Nurullina, Roza; Iljuhin, Aleksej (Journal of History Culture and Art Research, 2018)
The article investigates the state and dynamics of the national development and international relations in the course of 28 years in Tatarstan. It touches upon different and sometimes contradictory points of view on these processes. The article also represents the dynamics of the changes in the evaluation of these matters. Besides it studies the dynamics of opinions on issues related to the status of Tatarstan, the use of Tatar and Russian languages, etc. Methods of a longitudinal research allow making a comparative analysis of the empirical data that have been accumulating for several decades since 1989. The last empirical survey was conducted by us in 2017. This survey of Naberezhnye Chelny residents aged over 18 was carried out according to a stratified (regionalized) sample (n = 650), and ensured representativeness.